Anxiety among football school students in "Rector UNY Cup 2014" national tournament - Sulistyono, - (JOURNAL OF EDUCATION, 2015)
The study was aimed at explaining the anxiety level of Football School students who competed in "Rector UNY Cup 2014" national tournament. The  study was descriptive quantitative using purposive random sampling to obtain the subjects. Data were collected using the SCAT questionnaire. The results showed that, of the research participants, 43.27% had low anxiety, 53.13% had moderate anxiety, and 3.61% had high anxiety. On the average, the level of anxiety among the students who competed in the tournament was in the medium category. A possibleexplanation was that these students already had adequate experience from previouscompetitions. It seemed to be the case that these experiences had helped them toreduce anxiety despite the pressure to win the game